Portfolio of Online Distribution Channels across Mid-Market Hotels: An Evaluative Review - Sudipta Kumar Pal; Pallabi Mishra (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2017)
The purpose of this study is to provide an insight on current trend of research in the area of online channels for distribution of accommodation products across mid-market hotels from the hoteliers’ perspective and to suggest future research avenues. The study was based upon analysis of 12 relevant research papers published in peer-reviewed international tourism-hospitality journals during the period of 2004 - 2015. The selected papers were critically reviewed to update on ongoing researches in the area and to point out significant research gaps that indicated further research scopes. It is evident, online hotel booking is steadily growing since the inception of internet and its adaptation for distributing accommodation products by the lodging industry across the globe. Some studies attempted to determine the performance of online distribution channels (ODCs), as the choice of channels is critical for mid-market hotels in order to secure reservations and revenue. These hotels need to constitute a portfolio of ODCs to sustain and counter competition. The study sought to outline the existing strategies for managing distribution through online channels and subsequently to identify the areas of due attention. It may, therefore, provide new ideas to hospitality marketing managers and recommendations to academia for future research.